Weaving networks of learning and reflection: An innovative proposal for the Intergrated Master's Degree in Psychopedagogy - Margalef, Leonor; Iborra, Alejandro; Pareja, Natalie; Castro, Benjamin; Domínguez, Susana; García , Iván; Giménez, Salvador (Pulso. Revista de educación, 2007)
This paper recovers the experiences of a group of psycopedagogy teachers and students from the University of Alcala engaged in an innovative educational project developed under the framework of action research principles. Following the participative and shared spirit of this experience, the article is constructed around the contributions of some of the teachers and students involved in this project. The main objectives pursued were the construction of a learning and refl ection network that could facilitate an interdisciplinary approach as well as the generation of a favourable context for the development of teaching and learning processes founded in the principles of collaboration, autonomy and critical and refl ective thinking.
Keywords: Interdisciplinary Approach; Reflection; Selfdirected Learning; Collaborative Learning